Longitudinal changes of associations between the preproghrelin Leu72Met polymorphism with depression in Chinese Han adolescents after the Wenchuan earthquake. (October 2017) - Su, Mi; Cao, Ting; Feng, Yue; Guo, Qi W.; Fan, Mei; Fang, Ding Z.
Abstract : Aim: The present study aimed to investigate longitudinal associations of preproghrelin Leu72Met with depression in Chinese Han adolescents after the Wenchuan earthquake in 2008. Materials and methods: A total of 709 volunteers were enrolled from a high school near the epicenter of the earthquake and 662, 643, and 510 students were finally included at 6, 12, and 18 months, respectively, after the earthquake. Depressive symptoms were assessed using the Beck Depression Inventory (BDI). The genotypes were identified by PCR-restriction fragment length polymorphism analyses and verified by DNA sequencing. Results: Females had a higher prevalence of depression than males at 6 months after the earthquake in 72Leu/Leu homozygotes ( χ 2 -test, P =0.007), but not in 72Met allele carriers. 72Met allele carriers had lower prevalence ( χ 2 -test, P =0.025) and BDI scores (Kruskal–Wallis test, P= 0.034) than 72Leu/Leu homozygotes only among males at 18 months, but not at 6 or 12 months. The prevalence was consecutively decreased in male 72Met allele carriers ( χ 2 -test, P =0.010), but not in male 72Leu/Leu homozygotes, female 72Met allele carriers, or female 72Leu/Leu homozygotes during follow-up. Potential factors of depression prevalence and predictors of BDI scores were different between 72Leu/Leu homozygotes and 72Met allele carriers at different time points during follow-up. Conclusion: These results suggest that the 72Met allele of the preproghrelin Leu72Met polymorphism may be associated with rehabilitation of depression in male Chinese Han adolescents after the natural disaster.